POLITICAL STABILITY, MACRO ECONOMICS, AND ISLAMIC HUMAN DEVELOPMENT INDEX (I-HDI) IN OIC COUNTRIES - Kadir, Syahruddin; Abubakar, Achmad; Haddade, Hasyim; Ihsan, Akmal; Nur, Abustan (Jurnal Syarikah : Jurnal Ekonomi Islam, 2022)
The human development index set by UNDP seems to be no longer compatible and sufficient to measure development in Muslim countries because the Human Development Index is not based on an Islamic perspective, it is unable to capture the religious and ethical perspectives of socio-economic development. For this reason, a development called the Islamic Human Development Index emerged as a more complex human development index because it was derived from the five dimensions of maqāṣid syarī’ah, namely: religion (din), life (nafs), reason (aql), family (nasl), and wealth (mall). As the main reference (I-HDI), this study tries to explore the relationship between political stability, foreign direct investment, remittances, and unemployment, on the Islamic Human Development Index in Muslim countries in the world. The methodology used in this study is multiple linear regression with the Generalized Method of Moments (GMM) model and the assistance of Moderated Regression Analysis (MRA). The results of the study indicate that investments made by foreign countries to the world’s Islamic countries have a positive influence on Islamic human development. Likewise, remittances from overseas workers have a significant positive effect on the family’s economy, so that their needs are met. However, unemployment continues to be a big problem for Islamic human development, this is evidenced by statistical values that show a significant negative direction. In addition, based on the moderated regression analysis, political stability is included as a pure moderator, meaning that the existence of political stability can fully interact (strengthen) the relationship between foreign direct investment, remittances, and unemployment on the Islamic Human Development Index.